If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3) + 49 = 180 Reorder the terms: (3 + x) + 49 = 180 Remove parenthesis around (3 + x) 3 + x + 49 = 180 Reorder the terms: 3 + 49 + x = 180 Combine like terms: 3 + 49 = 52 52 + x = 180 Solving 52 + x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-52' to each side of the equation. 52 + -52 + x = 180 + -52 Combine like terms: 52 + -52 = 0 0 + x = 180 + -52 x = 180 + -52 Combine like terms: 180 + -52 = 128 x = 128 Simplifying x = 128
| -a+4+2a=7 | | 5x+8=8x+7 | | 18+2n=15+2n | | a-4a=2 | | 7(z-6)-(5+9z)=-3z | | 3(x+y)+3=-2x+y-10 | | -4+x=-2 | | 8x-3=-x | | -8x-9=3x+16 | | -2n=2 | | 3(x+5)+4(2y+3)=45 | | 2x+6y-5=0 | | -6+8p-7p+9=1+2p | | -6x-12y=30 | | 11+15y=7+13y | | -2x+2=-3x | | W^2+3w-12=0 | | X+2=67 | | 10-22=29-7x | | -2+42= | | -16x-9y+6=9 | | x^2=28x | | 9x-2=3(x+6)+6x | | -13y+84=6 | | 7y-9=-4-7y | | 11t=10t+16 | | 5x^2-19x=-14 | | 7p+10=7(-8p+4)+6(10+4p) | | 6x=7(x-9)+3 | | 9-(x-8)=-10 | | 69-34=5(x-3) | | 6x+1+7x=14 |